GOVERNMENTALITY IN SPINOZA’S POLITICA PHILOSOPY: ENQUIRG TO THE SPINOZA’S POLITICAL PHYLOSOPY THROUGHT THE CONCEPT GOVERNMENTALITY IN M. FOUCAULT - RODRÍGUEZ R., JOE STEVEN (Disertaciones, 2012)
In this article the reader will find the way Spinoza´s political philosophy gives an answer to the changing process of the practice of governing in centuries XV and XVI; the same process Foucault describes- in the College of France lecture during 1978- on the third conception of governmentality. We will present the way the deconstruction of the final cause produced the query of political conduction in men, which was aligned under a prerogative of administrative security that permitted the maintenance or state sustenance.